The Influence of Intellectual Capital, Capital Structure, Company Size, and Company Age on Agribusiness Financial Performance - Mursyidah, Faizah; Saleh, Suji Abdullah (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2023)
This research aims to determine the effect of intellectual capital, capital structure, firm size, and firm age on the financial performance of agricultural food product industry companies listed on the Indonesia Stock Exchange. Intellectual capital in this research is measured using the Pulic-Value Added Intellectual Coefficients (VAICTM) model, capital structure is measured by the Debt to Equity Ratio (DER), and the natural logarithm of total assets calculates the firm size. In contrast, healthy age is the years the company has been operating. Return on Assets (ROA) and Return on Equity (ROE) measure the company's financial performance. The sample in this research used a purposive sampling technique. This research uses secondary data from the sample companies' annual financial statements. The data analysis method used in this study is multiple regression analysis of panel data models. The results showed that intellectual capital has a significant positive effect on ROA and ROE, capital, firm size, and firm age do not affect ROA and ROE. Simultaneously, intellectual capital, capital structure, company size, and company age significantly affect ROA and ROE.